KEBERMANFAATAN INFORMASI AKUNTANSI BAGI INVESTOR UNTUK MENAKSIR RISIKO INVESTASI DI PASAR MODAL: SEBUAH TINJAUAN PUSTAKA - Budhi Purwantoro Jati (Akademi Akuntansi YKPN Yogyakarta, 2010)
Investors are one of the primary user groups of the financial statements, in making decisions they are interested in assessing the return and risk of their investment. There are two types of investmenst risk, firstly is systematic risk and secondly is unsystematic risk, however the relevant one for the investor is the systematic risk because it could not be prevented by diversifying the investment. This paper is intended to elaborate the two important analytical tools of accounting information which were proved to be useful in assessing the investment risk. Firstly is a financial ratio analysis and secondly is an empirical analysis.Keywords: accounting information, financial ratio, systematic risk.